Outdoor education program: assessing student performance, mental health, and teacher well-being - Wei, Shasha; Yang, Xiaoming; Ismail, Mohd H. B.; Farizan, Noor H.; Samsudin, Shamsulariffin (Duzce University, Faculty of Education, 2024)
Initiatives for outdoor education have gained popularity because of their capacity to boost teacher wellbeing, foster better mental health in instructors, and enrich the learning environment for students. We demonstrate the influence that outside education programs have on the achievement of students and how they create a vivid tapestry of hands-on experience that speeds up academic attainment through a thorough investigation of their educational achievement. Additionally, we investigate the important consequences for the mental wellness of students as well as the ways in which these programs support emotional health, self-worth, and stress reduction. This study contributes uniquely to the subject of education by highlighting the importance of educators especially and their critical role as facilitators of learning. The purpose of the research was to determine the relationship between students' well-being and academic performance and learning outdoors. The study looked into how instructors' well-being affected students' well-being and achievement in order to achieve this goal. The demographic group that is focused on consists of teachers, learners from intermediate school, supplementary, and college grades, as well as pertinent student data from various Chinese schools and institutions. With the use of Smart PLS, a modified least square structural equation modeling procedure was applied to the information collected from 250 participants. The study's findings are extremely pertinent to the field of education and offer a plethora of information to practitioners, decision-makers, and organizations. By understanding the major effect of outdoor education initiatives, we seek to provide the groundwork for innovative educational practices and policies that empower students, support instructors, and have long-lasting consequences. Further research is needed to identify more factors that improve academic achievement and wellness among students